Development of a Paper-Based Sol–Gel Vapochromic Sensor for the Detection of Vapor Cross-Contamination within a Closed Container - Janet Crespo-Cajigas; Abuzar Kabir; Joel Carrasco; Amatullah Shahid; Kenneth G. Furton; Lauryn E. DeGreeff (Analytica)
Contamination of trace levels of volatile organic compounds (VOCs) in enclosed spaces is not usually a significant cause for concern; however, it can be relevant in the case of canine scent detection training as a canine’s superior sense of smell makes them highly likely to detect low levels of contamination, contributing to inefficient training. Thus, herein, we address the need for a simple, low-cost, robust, vapochromic sensor to determine the cross-contamination of VOCs within closed containers, such as canine training aid kits. This study focuses on the development of a vapor sensor, which produces a rapid colorimetric change when a target chemical vapor is present. A pH indicator is used as the colorimetric dye and its incorporation into a sol–gel matrix on a paper substrate is confirmed via SEM characterization. The sensor’s stability and performance is tested against exposure to various levels of sunlight and temperature. The design allows the sensor to present a clear and unambiguous visible response to the release of the volatile target within a closed container. It can be readily incorporated into existing training kits and functions as a straightforward reminder of when training aids need to be changed or a new containment system should be considered.